ANALISIS PROFITABILITAS DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PERBANKAN PADA INDEKS INFOBANK15 - Yesyca, Yesyca; Harris, Ibnu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Universal, 2022)
A good capital structure describes a stable monetary condition, this means the company operational activities are going well, bringing maximal profit. This research is intended to empirically test the factors which affect the company’s banking modal structure in the index infobank15 using trade off theory and pecking order. This research use profitability variable and business risks as independent variable and modal structure as dependent variable. Profitability is measure with ROA and ROE. 53 samples are taken from 2015-2018. The analysis method is double regression and using company's yearly financial report. The results of F Test are 15,271 and F Table 2,79. This indicated the research model is still possible to be used. While the T per variable results for ROA variable and business risk don't have a significant Influence towards capital structure and ROE variable have a significant influence towards capital structure banking company in infobank15 index.